South African asset manager perceptions on the integration of climate change risks into equity investment decision-making processes - Ndebele, Nontokozo (GSB: Faculty, 2016)
The growing interest responsible investing strategies driven by bodies such as the United Nations Principles for Responsible Investing Initiative has resulted in issues such as climate change and its impact on investment portfolios becoming part of the asset management industry discourse. However, the degree to which these issues are perceived by asset managers to be significant has not been expanded upon extensively in literature. This study was undertaken to evaluate South African asset manager perceptions regarding the integration of climate change risks within equity investment decision-making processes. The study was further aimed at providing an understanding of preferred methods of climate change risk integration, where integration does take place, and the perceived barriers to integration within the South African Asset Management industry. To achieve the above-mentioned aims, an online survey of South African asset managers was conducted. The questions in the survey comprised a combination of open ended and closed ended questions with Likert and ranking scales being used. The data which was both quantitative and qualitative in nature was analysed using descriptive statistics and thematic analysis methods involving the identification of trends.